Proteomics discovery of MTDH and SND1 interaction vulnerabilities in ovarian cancer - Esmaeili, Parisa ; 0000-0002-4225-3298; Nasimian, Ahmad; Werner, Lucas; Junior, Sergio Mosquim ; 0000-0002-1537-7252; Jakobsson, Magnus E; Gerdtsson, Anna Sandström; Kazi, Julhash U ; 0000-0002-0719-5336; Levander, Fredrik ; 0000-0002-0710-9792 (Scientific Reports, 2025)
High-grade serous ovarian cancer (HGSOC) is the most prevalent and aggressive subtype of ovarian cancer. The combination of late-stage diagnosis and the tendency to exhibit resistance to existing treatments highlights a critical gap in effective therapeutic options. There is thus a need for novel strategies for targeting HGSOC, particularly in its advanced stages. To address this gap, we developed a comprehensive atlas profiling both the proteome and phosphoproteome levels across a panel of nine ovarian cancer cell lines from different subtypes. Subsequent differential expression analysis between the KURAMOCHI and the other cell lines, followed by phosphosite analyses, proposed the MTDH protein as a potential target. Further functional analyses of MTDH and the interacting protein SND1 with RNA silencing, as well as targeting their interaction, revealed that disrupting this interaction leads to the dysregulation of several pathways associated with cancer progression and invasion. In particular, interference with the MTDH-SND1 complex was associated with enrichment of ferroptosis-related pathways. Moreover, combining C26A6 treatment with ferroptosis inducers produced enhanced inhibitory effects in ovarian cancer cells, suggesting a possible strategy for targeting cancer cell vulnerabilities in HGSOC, which warrants further investigation beyond in vitro models.
© 2025. The Author(s).
Keywords: Humans; Female; Ovarian Neoplasms/metabolism; RNA-Binding Proteins; Membrane Proteins/metabolism; Proteomics/methods; Cell Line, Tumor; Cell Adhesion Molecules/metabolism; Gene Expression Regulation, Neoplastic; Nuclear Proteins/metabolism; Proteome; Endonucleases